Quantum Approach to Allergic Pathology - Spaggiari, Piergiorgio; Tribbia, Caterina; Gianpaolo, Pisano (Journal of Biotechnology and Biomedical Science, 2024)
Allergy, despite its stereotyped symptomatic manifestations, continues to pose significant etiological, pathophysiological, and therapeutic challenges. In the interface between the body and the environment, the respiratory pathway is particularly stressed from an allergological perspective. Under the relationship between energy and matter signed by Einstein, it is possible to approach patients suffering from allergies with an Electraceutical 1 administration in a quantum modality.
Keywords: Allergy; stereotyped symptomatic manifestations; pathophysiological; therapeutic challenges; Electraceutical